Low temperature spin-glass magnetic behavior of Ce3Pd20Ge6 - Gaidukov, Yu. P.; Nikiforov, V. N.; Koksharov, Yu. A.; Szymczak, R.; Szymczak, H.; Gribanov, A. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
A polycrystalline sample of Ce3Pd20Ge6 is investigated using a dc SQUID magnetometer. A noticeable difference between ZFC and FC magnetic susceptibility is found below approx60 K. The temperature dependence of the magnetic susceptibility demonstrates an anomaly near approximately 2.8K below which a remanent magnetic moment exists. Two characteristic temperatures detected support the assumption that there are different cerium magnetic subsystems in Ce3Pd20X6 (X= Ge,Si compounds. Unusual magnetic behavior observed in Ce3Pd20Ge6 is discussed within the framework of the &quotmolecular magnetism&quot model which predicts a frustration of exchange interactions.